Brokers of Public Trust Notaries in Early Modern Rome - Nussdorfer, Laurie (Johns Hopkins University Press, 2009)
A fast-growing legal system and economy in medieval and early modern Rome saw a rapid increase in the need for written documents. Brokers of Public Trust examines the emergence of the modern notarial profession-free market scribes responsible for producing original legal documents and their copies.Notarial acts often go unnoticed, but they are essential to understanding the history of writing practices and attitudes toward official documentation. Based on new archival research, Brokers of Public Trust focuses on the government officials, notaries, and consumers who regulated, wrote, and purchased notarial documents in Rome between the 14th and 18th centuries. Historian Laurie Nussdorfer chronicles the training of professional notaries and the construction of public archives, explaining why notarial documents exist, who made them, and how they came to be regarded as authoritative evidence. In doing so, Nussdorfer describes a profession of crucial importance to the people and government of the time, as well as to scholars who turn to notarial documents as invaluable and irreplaceable historical sources. This magisterial new work brings fresh insight into the essential functions of early modern Roman society and the development of the modern state.